Plasma ammonia levels in newborn infants admitted to an intensive care baby unit. Issue 7 (July 1980) - Beddis, I R; Hughes, E A; Rosser, E; Fenton, J C
Abstract : A fatal case associated with severe hyperammonaemia is described in which no urea cycle enzyme deficiency could be found. This prompted further investigation of blood ammonia levels in neonates admitted to the premature baby unit at Hammersmith Hospital. 102 specimens were taken from 42 babies within the first 3 weeks of life; the babies had a variety of clinical conditions. The mean ammonia level was 94.5 mumol/l (132.3 micrograms/100 ml) (range 32-255 mumol/l) (44.8-357 micrograms/ml), SD +/- 41.0). These results, although higher than the range for older babies in hospital, were not as high as in the baby with severe hyperammonaemia. Serial levels in 10 babies suggested that the range of blood ammonia levels was greatest in the first 2 weeks of life and narrowed considerably after this period. Great care is needed in collecting blood samples and measuring them if accuate results are to be obtained.